2011
DOI: 10.4049/jimmunol.1001407
|View full text |Cite
|
Sign up to set email alerts
|

T and B Cells Are Not Required for ClearingStaphylococcus aureusin Systemic Infection Despite a Strong TLR2–MyD88-Dependent T Cell Activation

Abstract: Staphylococcus aureus infection elicits through its mature lipoproteins an innate immune response by TLR2–MyD88 signaling, which improves bacterial clearing and disease outcome. The role of dendritic cells (DCs) and T cells in this immune activation and the function of T and B cells in defense against S. aureus infection remain unclear. Therefore, we first evaluated DC and T cell activation after infection with S. aureus wild type (WT) and its isogenic mutant, which is deficient in lipoprotein maturation, in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 61 publications
8
44
0
Order By: Relevance
“…To further clarify the mechanism by which S. aureus promotes maturation of DCs, we examined the role of the MyD88 signaling pathway, a critical pathway activated by TLR stimulation in innate immune cells (21). It has also been reported that MyD88 is required for TLR signal transduction in mouse DCs in response to S. aureus (22,23). Therefore, we assessed whether the activation of human blood BDCA1 ϩ mDCs by S. aureus is dependent on the MyD88 signaling pathway.…”
Section: S Aureus-induced Bdca1mentioning
confidence: 99%
“…To further clarify the mechanism by which S. aureus promotes maturation of DCs, we examined the role of the MyD88 signaling pathway, a critical pathway activated by TLR stimulation in innate immune cells (21). It has also been reported that MyD88 is required for TLR signal transduction in mouse DCs in response to S. aureus (22,23). Therefore, we assessed whether the activation of human blood BDCA1 ϩ mDCs by S. aureus is dependent on the MyD88 signaling pathway.…”
Section: S Aureus-induced Bdca1mentioning
confidence: 99%
“…The results of one representative experiment are presented; each was repeated at least once. mutant S. aureus strains but not wild-type isolates elicit adaptive immunity against S. aureus sepsis in single strains of mice (19)(20)(21)(22). Therefore, our model, in which a natural SSTI with a wild-type S. aureus clinical isolate elicited protective immunity in BALB/c but not C57BL/6 mice, afforded us a unique opportunity to dissect the determinants of protection against recurrent infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, C57BL/6 mice become completely susceptible to S. aureus when neutrophils are depleted or neutrophil recruitment is blocked. Furthermore, the resistance is shown not to be dependent on T or B cells, indicating that neutrophils are essential (36,44). Since the KI mice had lower body weights than wild-type mice of similar age, the sizes of the inocula were normalized on the basis of body weight (1.82 ϫ 10 6 CFU/g of body weight).…”
Section: Resultsmentioning
confidence: 99%